THE INFLUENCE OF PRICE EARNINGS RATIO, PRICE TO BOOK VALUE, AND RETURN ON EQUITY ON STOCK RETURNS IN COMPANIES CONDUCTING INITIAL PUBLIC OFFERINGS FOR THE 2022-2023 PERIOD - Napitupulu, Dongani; Sibarani, Mentiana; Rahmat, Damianus Tulus (Ridwan Institute, 2024)
This study aims to analyze the effect of financial ratios such as PER, PBV, and ROE on stock returns in companies that have just conducted an IPO in the 2022-2023 period. The research population consists of companies that conducted IPOs on the Indonesia Stock Exchange (IDX) in the period July 2022 to July 2023. The study population was taken using the purposive random sampling method, which combines purposively sampling with a randomization process, to ensure valid representation. This study uses data on the financial statements of companies listed on the IDX during the period 2022-23. Based on the results of the research that has been conducted, it can be concluded that there is a significant influence between financial ratio and stock returns. The regression model developed was able to explain about 42.5% of the total variation in stock returns, showing that the independent variables used made a significantly contribution in explaining the fluctuations in stock return. This research could offer valuable implications for investors in evaluating IPO companies and assist companies in maintaining high profitability and good market reputation before going public. Moreover, findings could inform capital market regulators in developing policies aimed at enhancing investor protection and market efficiency.